Microbial Diversity Analysis and Genome Sequencing Identify Xanthomonas perforans as the Pathogen of Bacterial Leaf Canker of Water Spinach (Ipomoea aquatic) - Hu, Ming; Li, Chuhao; Zhou, Xiaofan; Xue, Yang; Wang, Si; Hu, Anqun; Chen, Shanshan; Mo, Xiuwen; Zhou, Jianuan (Frontiers in Microbiology, 2021)
Ipomoea aquatica is a leafy vegetable widely cultivated in tropical Asia, Africa, and Oceania. Bacterial leaf canker disease has been attacking the planting fields and seriously affecting the quality of I. aquatica in epidemic areas in China. This study examined the microbial composition of I. aquatica leaves with classical symptoms of spot disease. The results showed that Xanthomonas was overwhelmingly dominant in all four diseased leaf samples but rarely present in rhizospheric soil or irrigation water samples. In addition, Pantoea was also detected in two of the diseased leaf samples. Pathogen isolation, identification, and inoculation revealed that both Xanthomonas sp. TC2-1 and P. ananatis were pathogenic to the leaves of I. aquatic, causing crater-shaped ulcerative spots and yellowing with big brown rot lesions on leaves, respectively. We further sequenced the whole genome of strain TC2-1 and showed that it is a member of X. perforans. Overall, this study identified X. perforans as the causal pathogen of I. aquatica bacterial leaf canker, and P. ananatis as a companion pathogen causing yellowing and brown rot on leaves. The correct identification of the pathogens will provide important basis for future efforts to formulate targeted application strategy for bacterial disease control.